Observing Planetary and Pre-Planetary Nebulae with the James Webb Space Telescope - Raghvendra Sahai (Galaxies, 2020)
Most stars in the Universe that leave the main sequence in a Hubble time will end their lives evolving through the Planetary Nebula (PN) evolutionary phase. The heavy mass loss which occurs during the preceding Asymptotic Giant Branch (AGB) phase is important across astrophysics, dramatically changing the course of stellar evolution, contributing to the dust content of the interstellar medium, and influencing its chemical composition. The evolution from the AGB phase to the PN phases remains poorly understood, especially the dramatic transformation that occurs in the morphology of the mass-ejecta as AGB stars enter the post-AGB phase and their round circumstellar envelopes evolve into pre-PNe (PPNe) and then to PNe. The majority of PPNe and PNe deviate strongly from spherical symmetry. Strong binary interactions most likely play a fundamental role in influencing this evolutionary phase, but the details of these interactions remain shrouded in mystery. Thus, understanding the formation and evolution of these objects is of wide astrophysical importance. PNe have long been known to emit across a very large span of wavelengths, from the radio to X-rays. Extensive use of space-based observatories at X-ray (Chandra/ XMM-Newton), optical (HST) and mid- to far-infrared (Spitzer, Herschel) wavelengths in recent years has produced significant new advances in our knowledge of these objects. Given the expected advent of the James Webb Space Telescope (JWST) in the near future, we focus on future high-angular-resolution, high-sensitivity observations at near and mid-IR wavelengths with JWST that can help in addressing the major unsolved problems in the study of PNe and their progenitors.